1977
DOI: 10.1159/000275366
|View full text |Cite
|
Sign up to set email alerts
|

Prednisone in Idiopathic Facial Paralysis (Bell’s Palsy)

Abstract: 76 patients with severe Bell’s palsy were treated for a short period with high doses of prednisone (60 mg for 4 days and from the 5th day on the dose was reduced every day by 5 mg). The treatment was started within the 1st week of onset. The onset, the course and the recovery of the paralysis were carefully evaluated. The facial recovery is presented in such way as to make possible comparison with other series of recovery after Bell’s palsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

1984
1984
2010
2010

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…Patients often recall cooling of the face or a cold draught just before the outburst of the facial palsy. BP following airplane trips has also been reported [3]. Experimental data support a hypothesis of low temperatures in the pathogenesis of BP [15-18].…”
Section: Introductionmentioning
confidence: 71%
See 2 more Smart Citations
“…Patients often recall cooling of the face or a cold draught just before the outburst of the facial palsy. BP following airplane trips has also been reported [3]. Experimental data support a hypothesis of low temperatures in the pathogenesis of BP [15-18].…”
Section: Introductionmentioning
confidence: 71%
“…Devriese (1977) investigated the relationship between atmospheric pressure and facial nerve palsy in a three-year study period. His statistical analysis, based on recordings of short time pressure changes, changes in two days, and the stability of atmospheric pressure changes within two days, failed to show a positive association between atmospheric pressure changes and the occurrence of BP [3]. In search for a relationship between weather conditions and facial nerve palsy, Herbert et al demonstrated a significant increment in the incidence of the disease on days with low barometric pressure, especially when a low barometric pressure period follows a high one, thus creating great pressure differences [33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meteorological changes and air pollution are the most common parameters analyzed. However, despite the fact that interest about this field has been increasing in recent years, we have only found one report in the current English literature on this topic concerning Bell's palsy [4].…”
Section: Discussionmentioning
confidence: 86%
“…In a previous study, the onset of idiopathic facial paralysis (Bell's palsy) in 241 patients, observed over a 3-year period, was also examined in relation to atmospheric pressure. In that paper, the hypothesis of no association was not rejected [4].…”
Section: Discussionmentioning
confidence: 90%